Transforming Combustion Research through Cyberinfrastructure - National Research Council (The National Academies Press, 2011)
Combustion has provided society with most of its energy needs for millenia, from igniting the fires of cave dwellers to propelling the rockets that traveled to the Moon. Even in the face of climate change and the increasing availability of alternative energy sources, fossil fuels will continue to be used for many decades. However, they will likely become more expensive, and pressure to minimize undesired combustion by-products (pollutants) will likely increase. The trends in the continued use of fossil fuels and likely use of alternative combustion fuels call for more rapid development of improved combustion systems. In January 2009, the Multi-Agency Coordinating Committee on Combustion Research (MACCCR) requested that the National Research Council (NRC) conduct a study of the structure and use of a cyberinfrastructure (CI) for combustion research. The charge to the authoring committee of Transforming Combustion Research through Cyberinfrastructure was to: identify opportunities to improve combustion research through computational infrastructure (CI) and the potential benefits to applications; identify necessary CI elements and evaluate the accessibility, sustainability, and economic models for various approaches; identify CI that is needed for education in combustion science and engineering; identify human, cultural, institutional, and policy challenges and how other fields are addressing them. Transforming Combustion Research through Cyberinfrastructure also estimates the resources needed to provide stable, long-term CI for research in combustion and recommends a plan for enhanced exploitation of CI for combustion research.

Relieving Pain in America: A Blueprint for Transforming Prevention, Care, Education, and Research - Institute of Medicine (The National Academies Press, 2011)
Chronic pain costs the nation up to 635 billion each year in medical treatment and lost productivity. The 2010 Patient Protection and Affordable Care Act required the Department of Health and Human Services (HHS) to enlist the Institute of Medicine (IOM) in examining pain as a public health problem. In this report, the IOM offers a blueprint for action in transforming prevention, care, education, and research, with the goal of providing relief for people with pain in America. To reach the vast multitude of people with various types of pain, the nation must adopt a population-level prevention and management strategy. The IOM recommends that HHS develop a comprehensive plan with specific goals, actions, and timeframes. Better data are needed to help shape efforts, especially on the groups of people currently underdiagnosed and undertreated, and the IOM encourages federal and state agencies and private organizations to accelerate the collection of data on pain incidence, prevalence, and treatments. Because pain varies from patient to patient, healthcare providers should increasingly aim at tailoring pain care to each person's experience, and self-management of pain should be promoted. In addition, because there are major gaps in knowledge about pain across health care and society alike, the IOM recommends that federal agencies and other stakeholders redesign education programs to bridge these gaps. Pain is a major driver for visits to physicians, a major reason for taking medications, a major cause of disability, and a key factor in quality of life and productivity. Given the burden of pain in human lives, dollars, and social consequences, relieving pain should be a national priority.

Preventing Violence Against Women and Children: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Violence against women and children is a serious public health concern, with costs at multiple levels of society. Although violence is a threat to everyone, women and children are particularly susceptible to victimization because they often have fewer rights or lack appropriate means of protection. In some societies certain types of violence are deemed socially or legally acceptable, thereby contributing further to the risk to women and children. In the past decade research has documented the growing magnitude of such violence, but gaps in the data still remain. Victims of violence of any type fear stigmatization or societal condemnation and thus often hesitate to report crimes. The issue is compounded by the fact that for women and children the perpetrators are often people they know and because some countries lack laws or regulations protecting victims. Some of the data that have been collected suggest that rates of violence against women range from 15 to 71 percent in some countries and that rates of violence against children top 80 percent. These data demonstrate that violence poses a high burden on global health and that violence against women and children is common and universal. Preventing Violence Against Women and Children focuses on these elements of the cycle as they relate to interrupting this transmission of violence. Intervention strategies include preventing violence before it starts as well as preventing recurrence, preventing adverse effects (such as trauma or the consequences of trauma), and preventing the spread of violence to the next generation or social level. Successful strategies consider the context of the violence, such as family, school, community, national, or regional settings, in order to determine the best programs.

Public Transportation Systems as the Foundation for Economic Growth - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2011)
TRB2019s Transit Cooperative Research Program (TCRP) RRD 102: Public Transportation Systems as the Foundation for Economic Growth examines how transit investments are linked to economic growth and recovery in several cities in Turkey, Egypt, and South Africa.

Intelligence Analysis: Behavioral and Social Scientific Foundations - National Research Council (The National Academies Press, 2011)
The U.S. intelligence community (IC) is a complex human enterprise whose success depends on how well the people in it perform their work. Although often aided by sophisticated technologies, these people ultimately rely on their own intellect to identify, synthesize, and communicate the information on which the nation's security depends. The IC's success depends on having trained, motivated, and thoughtful people working within organizations able to understand, value, and coordinate their capabilities. Intelligence Analysis provides up-to-date scientific guidance for the intelligence community (IC) so that it might improve individual and group judgments, communication between analysts, and analytic processes. The papers in this volume provide the detailed evidentiary base for the National Research Council's report, Intelligence Analysis for Tomorrow: Advances from the Behavioral and Social Sciences. The opening chapter focuses on the structure, missions, operations, and characteristics of the IC while the following 12 papers provide in-depth reviews of key topics in three areas: analytic methods, analysts, and organizations. Informed by the IC's unique missions and constraints, each paper documents the latest advancements of the relevant science and is a stand-alone resource for the IC's leadership and workforce. The collection allows readers to focus on one area of interest (analytic methods, analysts, or organizations) or even one particular aspect of a category. As a collection, the volume provides a broad perspective of the issues involved in making difficult decisions, which is at the heart of intelligence analysis.

The Health of Lesbian, Gay, Bisexual, and Transgender People: Building a Foundation for Better Understanding - Institute of Medicine (The National Academies Press, 2011)
At a time when lesbian, gay, bisexual, and transgender individuals2014often referred to under the umbrella acronym LGBT2014are becoming more visible in society and more socially acknowledged, clinicians and researchers are faced with incomplete information about their health status. While LGBT populations often are combined as a single entity for research and advocacy purposes, each is a distinct population group with its own specific health needs. Furthermore, the experiences of LGBT individuals are not uniform and are shaped by factors of race, ethnicity, socioeconomic status, geographical location, and age, any of which can have an effect on health-related concerns and needs. The Health of Lesbian, Gay, Bisexual, and Transgender People assesses the state of science on the health status of LGBT populations, identifies research gaps and opportunities, and outlines a research agenda for the National Institute of Health. The report examines the health status of these populations in three life stages: childhood and adolescence, early\/middle adulthood, and later adulthood. At each life stage, the committee studied mental health, physical health, risks and protective factors, health services, and contextual influences. To advance understanding of the health needs of all LGBT individuals, the report finds that researchers need more data about the demographics of these populations, improved methods for collecting and analyzing data, and an increased participation of sexual and gender minorities in research. The Health of Lesbian, Gay, Bisexual, and Transgender People is a valuable resource for policymakers, federal agencies including the National Institute of Health (NIH), LGBT advocacy groups, clinicians, and service providers.

Communicating National Science Foundation Science and Engineering Information to Data Users: Letter Report - National Research Council (The National Academies Press, 2011)
This report from the Panel on Communicating National Science Foundation (NSF) Science and Engineering Information to Data Users recommends action by the National Center for Science and Engineering Statistics (SRS) on four key issues: data content and presentation; meeting changing storage and retrieval standards; understanding data users and their emerging needs; and data accessibility. This report also includes a summary of the workshop that focused on the several aspects of the NCSES's current approaches to communicating and disseminating statistical information – including NCSES's information products, website, and database systems. It included presentations from NCSES staff and representatives of key use groups – including the academic research, private nonprofit research, and federal government policy making communities.

Allied Health Workforce and Services: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
The demand for health care is growing as the nation ages and seeks to provide coverage for the millions of Americans who lack health insurance. At the same time, escalating costs have led to a variety of initiatives to make the delivery of health care more effective and efficient. The allied health workforce is critical to the success of these efforts. The IOM held a workshop May 9-10, 2011, to examine the current allied health care workforce and consider how it can contribute to improving health care access, quality, and effectiveness.

Strategies to Attract and Retain a Capable Transportation Workforce - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2011)
TRB2019s National Cooperative Highway Research Program (NCHRP) Report 685: Strategies to Attract and Retain a Capable Transportation Workforce includes straight-forward, implementable practices that transportation Human Resources (HR) managers and hiring professionals can use to help improve the recruitment and retention of qualified employees in their organizations.The report provides information on workforce challenges, industry strategies, and detailed descriptions of noteworthy practices within each of 15 recruitment and retention categories.Volume II: Supplemental Material is available online as an ISO image, which can be used to produce a CD-ROM. Volume II includes an introductory document summarizing the content of the supplemental materials and provides full case studies and summaries of other example practices related to the recruitment and retention practices.Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.Help on Burning an .ISO CD-ROM ImageDownload the .ISO CD-ROM Image(Warning: This is a large file and may take some time to download using a high-speed connection.)CD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively 201cTRB2019) be liable for any loss or damage caused by the installation or operations of this product. TRB makes no representation or warrant of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.

Digital Infrastructure for the Learning Health System: The Foundation for Continuous Improvement in Health and Health Care: Workshop Series Summary - Institute of Medicine (The National Academies Press, 2011)
Like many other industries, health care is increasingly turning to digital information and the use of electronic resources. The Institute of Medicine's Roundtable on Value & Science-Driven Health Care hosted three workshops to explore current efforts and opportunities to accelerate progress in improving health and health care with information technology systems.

Naval Engineering in the 21st Century: The Science and Technology Foundation for Future Naval Fleets – Special Report 306 - Transportation Research Board (The National Academies Press, 2011)
TRB Special Report 306: Naval Engineering in the 21st Century: The Science and Technology Foundation for Future Naval Fleets examines the state of basic and applied research in the scientific fields that support naval engineering and explores whether Office of Naval Research (ONR) activities, under its National Naval Responsibility for Naval Engineering (NNR-NE) initiative, have been effective in sustaining these fields. The committee developed a series of conclusions and recommendations in five areas–the value of the NNR-NE, the state of science and technology supporting naval engineering, the wholeness of the NNR-NE research portfolio, opportunities for enhancement of research and education, and the effectiveness of the NNR-NE initiative. The report's recommendations are addressed to the administrators of the NNR-NE initiative and of ONR.

Design Guidelines for Increasing the Lateral Resistance of Highway-Bridge Pile Foundations by Improving Weak Soils - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2011)
TRB2019s National Cooperative Highway Research Program (NCHRP) Report 697: Design Guidelines for Increasing the Lateral Resistance of Highway-Bridge Pile Foundations by Improving Weak Soils examines guidance for strengthening of soils to resist lateral forces on bridge pile foundations.The report presents computational methods for assessing soil-strengthening options using finite-element analysis of single piles and pile groups and a simplified approach employing commercially available software.

Early Childhood Obesity Prevention Policies - Institute of Medicine (The National Academies Press, 2011)
Childhood obesity is a serious health problem that has adverse and long-lasting consequences for individuals, families, and communities. The magnitude of the problem has increased dramatically during the last three decades and, despite some indications of a plateau in this growth, the numbers remain stubbornly high. Efforts to prevent childhood obesity to date have focused largely on school-aged children, with relatively little attention to children under age 5. However, there is a growing awareness that efforts to prevent childhood obesity must begin before children ever enter the school system. Early Childhood Obesity Prevention Policies reviews factors related to overweight and obese children from birth to age 5, with a focus on nutrition, physical activity, and sedentary behavior, and recommends policies that can alter children's environments to promote the maintenance of healthy weight. Because the first years of life are important to health and well-being throughout the life span, preventing obesity in infants and young children can contribute to reversing the epidemic of obesity in children and adults. The book recommends that health care providers make parents aware of their child's excess weight early. It also suggests that parents and child care providers keep children active throughout the day, provide them with healthy diets, limit screen time, and ensure children get adequate sleep. In addition to providing comprehensive solutions to tackle the problem of obesity in infants and young children, Early Childhood Obesity Prevention Policies identifies potential actions that could be taken to implement those recommendations. The recommendations can inform the decisions of state and local child care regulators, child care providers, health care providers, directors of federal and local child care and nutrition programs, and government officials at all levels.

Planning a WIC Research Agenda: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
The time has come to initiate a new program of research on the Supplemental Nutrition Program for Women, Infants, and Children (commonly referred to as WIC). WIC is the third largest food assistance program administered by the U.S. Department of Agriculture (USDA). The program's scope is large, serving approximately 9.3 million low-income women, infants, and children at nutritional risk. Through federal grants to states, participants receive three types of benefits: 1) a supplemental food package tailored to specific age groups for infants and children; 2) nutrition education, including breastfeeding support; and 3) referrals to health services and social services. To cover program costs for fiscal year (FY) 2010, Congress appropriated 7.252 billion. Congress also appropriated 15 million for research related to the program for FY 2010. The timing of the funding for WIC research is propitious. In October 2009, USDA issued regulations that made substantial revisions to the WIC food package. These revisions are the first major change in the food package since the program's inception in 1972. Over the intervening years WIC has expanded greatly, Medicaid coverage has increased, large changes have occurred in the racial and ethnic backgrounds and socioeconomic status of WIC participants as well as in public health services, and obesity rates have increased substantially among the general population. To guide its planning for the use of the 15 million allocated for WIC research, the Food and Nutrition Service of USDA asked the Institute of Medicine to conduct a two-day public workshop on emerging research needs for WIC. As requested, the workshop included presentations and discussions to illuminate issues related to future WIC research issues, methodological challenges, and solutions. The workshop also planned for a program of research to determine the effects of WIC on maternal and child health outcomes.

Improving Access to Oral Health Care for Vulnerable and Underserved Populations - Institute of Medicine; National Research Council (The National Academies Press, 2011)
Access to oral health care is essential to promoting and maintaining overall health and well-being, yet only half of the population visits a dentist each year. Poor and minority children are less likely to have access to oral health care than are their nonpoor and nonminority peers. Older adults, people who live in rural areas, and disabled individuals, uniformly confront access barriers, regardless of their financial resources. The consequences of these disparities in access to oral health care can lead to a number of conditions including malnutrition, childhood speech problems, infections, diabetes, heart disease, and premature births. Improving Access to Oral Health Care for Vulnerable and Underserved Populations examines the scope and consequences of inadequate access to oral health services in the United States and recommends ways to combat the economic, structural, geographic, and cultural factors that prevent access to regular, quality care. The report suggests changing funding and reimbursement for dental care; expanding the oral health work force by training doctors, nurses, and other nondental professionals to recognize risk for oral diseases; and revamping regulatory, educational, and administrative practices. It also recommends changes to incorporate oral health care into overall health care. These recommendations support the creation of a diverse workforce that is competent, compensated, and authorized to serve vulnerable and underserved populations across the life cycle. The recommendations provided in Improving Access to Oral Health Care for Vulnerable and Underserved Populations will help direct the efforts of federal, state, and local government agencies; policy makers; health professionals in all fields; private and public health organizations; licensing and accreditation bodies; educational institutions; health care researchers; and philanthropic and advocacy organizations.

The Future of Nursing: Leading Change, Advancing Health - Institute of Medicine (The National Academies Press, 2011)
The Future of Nursing explores how nurses' roles, responsibilities, and education should change significantly to meet the increased demand for care that will be created by health care reform and to advance improvements in America's increasingly complex health system. At more than 3 million in number, nurses make up the single largest segment of the health care work force. They also spend the greatest amount of time in delivering patient care as a profession. Nurses therefore have valuable insights and unique abilities to contribute as partners with other health care professionals in improving the quality and safety of care as envisioned in the Affordable Care Act (ACA) enacted this year. Nurses should be fully engaged with other health professionals and assume leadership roles in redesigning care in the United States. To ensure its members are well-prepared, the profession should institute residency training for nurses, increase the percentage of nurses who attain a bachelor's degree to 80 percent by 2020, and double the number who pursue doctorates. Furthermore, regulatory and institutional obstacles2014including limits on nurses' scope of practice2014should be removed so that the health system can reap the full benefit of nurses' training, skills, and knowledge in patient care. In this book, the Institute of Medicine makes recommendations for an action-oriented blueprint for the future of nursing.

Child and Adult Care Food Program: Aligning Dietary Guidance for All - Institute of Medicine (The National Academies Press, 2011)
The Child and Adult Care Food Program (CACFP) is a federally-funded program designed to provide healthy meals and snacks to children and adults while receiving day care at participating family day care homes, traditional child care centers, afterschool facilities, adult care facilities, and emergency shelters. CACFP has the broadest scope of any of the U.S. Department of Agriculture (USDA) food program, serving more than 3 million children and 114,000 adults across the nation. To receive reimbursement for the foods served, participating programs must abide by requirements set by the USDA. Child and Adult Care Food Program assesses the nutritional needs of the CACFP population based on Dietary Guidelines for Americans and the Dietary Reference Intakes (DRIs) and makes recommendations for revisions to the CACFP meal requirements. The book outlines meal requirements that include food specifications that could be used for specific meals and across a full day, covering all age groups from infants to older adults and meal patterns designed for use in a variety of settings, including in-home care and in large centers. By implementing these meal requirements, consumption of fruits, vegetables, and whole-grain rich foods will increase while consumption of solid fats, added sugars, and sodium will decrease. Not only will this address the high prevalence of childhood obesity, it will also help to achieve consistency with the standards and regulations of other USDA nutrition assistance programs, particularly the Supplemental Nutrition Program for Women, Infants, and Children (WIC), and the National School Lunch and School Breakfast programs. Child and Adult Care Food Program makes practical recommendations that would bring CACFP meals and snacks into alignment with current dietary guidance. The book will serve as a vital resource for federal and state public health officials, care providers working in child and adult day care facilities, WIC agencies, officials working with the National School Lunch and School Breakfast programs, and other organizations serving at-risk populations.

Sociocultural Data to Accomplish Department of Defense Missions: Toward a Unified Social Framework: Workshop Summary - National Research Council (The National Academies Press, 2011)
Sociocultural Data to Accomplish Department of Defense Missions: Toward a Unified Social Framework summarizes presentations and discussions that took place on August 16-17, 2010, at a National Research Council public workshop sponsored by the Office of Naval Research. The workshop addressed the variables and complex interaction of social and cultural factors that influence human behavior, focusing on potential applications to the full spectrum of military operations. The workshop's keynote address by Major General Michael T. Flynn, U.S. Army, provided critical context about the cultural situation and needs of the military operating in Afghanistan. Additional presentations were divided into four panels to address the diverse missions encountered by the U.S. military worldwide. The workshop concluded with a final panel to discuss the strengths and weaknesses of different methods of acquiring and using relevant data and knowledge to accomplish these missions. The panel topics and presenters are listed below: Conflict Is Local: Mapping the Sociocultural Terrain David Kennedy, Hsinchun Chen, and Kerry Patton Bridging Sociocultural Gaps in Cooperative Relationships Robert Rubinstein, Alan Fiske, and Donal Carbaugh Building Partner Capacity with Sociocultural Awareness Jeffrey Sanchez-Burks and Shinobu Kitayama The Art of Sociocultural Persuasion Jeanne Brett, James Dillard, and Brant R. Burleson Tools, Methods, Frameworks, and Models Mark Bevir, Laura A. McNamara, Robert G. Sargent, and Jessica Glicken Turnley

Legal Strategies in Childhood Obesity Prevention: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Since 1980, childhood obesity rates have more than tripled in the United States. Recent data show that almost one-third of children over 2 years of age are already overweight or obese. While the prevalence of childhood obesity appears to have plateaued in recent years, the magnitude of the problem remains unsustainably high and represents an enormous public health concern. All options for addressing the childhood obesity epidemic must therefore be explored. In the United States, legal approaches have successfully reduced other threats to public health, such as the lack of passive restraints in automobiles and the use of tobacco. The question then arises of whether laws, regulations, and litigation can likewise be used to change practices and policies that contribute to obesity. On October 21, 2010, the Institute of Medicine (IOM) held a workshop to bring together stakeholders to discuss the current and future legal strategies aimed at combating childhood obesity. Legal Strategies in Childhood Obesity Prevention summarizes the proceedings of that workshop. The report examines the challenges involved in implementing public health initiatives by using legal strategies to elicit change. It also discusses circumstances in which legal strategies are needed and effective. This workshop was created only to explore the boundaries of potential legal approaches to address childhood obesity, and therefore, does not contain recommendations for the use of such approaches.

Research Training in the Biomedical, Behavioral, and Clinical Research Sciences - National Research Council (The National Academies Press, 2011)
Comprehensive research and a highly-trained workforce are essential for the improvement of health and health care both nationally and internationally. During the past 40 years the National Research Services Award (NRSA) Program has played a large role in training the workforce responsible for dramatic advances in the understanding of various diseases and new insights that have led to more effective and targeted therapies. In spite of this program, the difficulty obtaining jobs after the postdoc period has discouraged many domestic students from pursuing graduate postdoc training. In the United States, more than 50 percent of the postdoc workforce is made up of individuals who obtained their Ph.D.s from other countries. Indeed, one can make a strong argument that the influx of highly trained and creative foreigners has contributed greatly to U.S. science over the past 70 years. Research Training in the Biomedical, Behavioral, and Clinical Research Sciences discusses a number of important issues, including: the job prospects for postdocs completing their training; questions about the continued supply of international postdocs in an increasingly competitive world; the need for equal, excellent training for all graduate students who receive NIH funding; and the need to increase the diversity of trainees. The book recommends improvements in minority recruiting, more rigorous and extensive training in the responsible conduct of research and ethics, increased emphasis on career development, more attention to outcomes, and the requirement for incorporating more quantitative thinking in the biomedical curriculum.